METHODOLOGICAL BASES OF EFFICIENCY ASSESSMENT OF UNIVERSITY SCIENCE INTEGRATION IN NATIONAL INNOVATION SYSTEM OF THE RUSSIAN FEDERATION - E. Belova (Вестник университета, 2017)
In the condition of scientifical educational formation of Russian Federation, methodological approaches to the development of the university's scientific activities into the national innovation system of the country are still specifying. The system of figures and methods of innovative potential of Russian Universities are proposed. Selection and justification methods of development strategy of Universities in the national innovation system is presented.